IMPROVING THE FURNITURE SUPPLY CHAIN BY LEARNING FROM OTHER INDUSTRIES - Boone, Nicholas (Production engineering and management proceedings 3rd international conference 26th and 27th September 2013 Trieste, Italy)
Based on literature research, this paper tries to identify supply chain relevant trends in the furniture industry. Also, the situation in the furniture Industry is compared to that of the automotive and the Fast Moving Consumer Goods industry in order to see if some of the successful supply chain strategies in these industries can be transferred. Key findings are that supply chain measures are often underestimated, both on the retail and on the manufacturer side. The furniture industry is found to lack standards in IT, processes and handling equipment. However, there is growing consensus that integrated processes are extremely important for a company's business success.